ANALISIS IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK DALAM MENGATASI KASUS BULLYING DI SDN 3 PANCOR - Husnawati; Siti Zainab Muslimin; Halimatussa’diah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Husnawati (NIM :2102604118) This study aims to analyze the implementation of the Child-Friendly School (CFS) program in addressing bullying cases at SDN 3 Pancor. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The focus of the study includes three main aspects: (1) the system and procedures of implementing the Child-Friendly School program in addressing bullying, (2) the role of teachers in preventing and handling bullying, and (3) the supporting and inhibiting factors in the implementation of the Child-Friendly School program at the school. The results of the study indicate that the implementation of the Child-Friendly School program at SDN 3 Pancor has been carried out quite well through the application of values such as respect for children's rights, enjoyable learning, and the active involvement of students and parents in school activities. Teachers play an important role as role models, supervisors, and mediators in managing student conflicts and guiding them toward positive behavior. The supporting factors of the program include the principal’s support, collaboration between teachers and parents, and a conducive school environment. Meanwhile, the inhibiting factors include students’ difficult behavior, lack of parental awareness, and limited supporting facilities. Overall, the Child-Friendly School program has contributed positively to reducing bullying behavior and creating a safer, more comfortable, and enjoyable learning environment for all students at SDN 3 Pancor.